Usulan Tata Letak Pabrik Dengan Menggunakan Metode Aldep - Mela Pebriyani; Winarno Winarno (Peneliti.net, 2022)
PT XYZ is a company engaged in manufacturing with motor vehicle spare parts and diesel products. In a company, layout planning is an important part that must be considered. This is due to an unfavorable layout that will hinder the flow of materials, production, information and labor so that it will increase production costs. Constraints faced by PT. XYZ is that there is no update regarding the layout of the existing facilities. So that the state of the company directly and the depiction of the company in the form of a layout is not the same. So this study aims to determine the facilities that have not been included in the overall company layout drawing, changes to the facility layout, and the best facility layout for PT.XYZ. From the data processing, there are 3 rooms that were studied using the ALDEP method, production 1, production 2 and die maker/work shop . Die maker as the beginning of the start of data processing makes the space with the smallest calculation score of -15055. The value obtained is not perfect, but the score is the score closest to the positive value or the number 0 (zero). So it was chosen as the best layout among the other rooms studied.